Interaction Between Religion and Philosophy - Zaprulkhan, Zaprulkhan (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2019)
The relationship between religion and philosophy, in the view of experts, has similarities as well as differences. Religion and philosophy in grasping the truth have several similarities and differences. In religion, true truth must be guided by revelation or belief. The use of reason is only to enrich the analysis of truth. Whereas in philosophy, truth must be approached using reason through a process of reasoning. Although the truth presented by religion may be similar to the truth achieved by philosophy, religion still cannot be equated with philosophy. This difference is due to a different perspective. This article will focus on the relationship between religion and philosophy. There are several paradigms that are presented about the relationship of religion and philosophy including paradigms of contrast, subordinative, and integralistic. This paper will take the position of integrative paradigm.